A formação de professores de matemática no contexto da resolução de problemas - Justulin, Andresa Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The purpose of the present study was to investigate teachers' professional learning that arises in a study group grounded on Methodology of Mathematics Teaching-Learning-Evaluation through Problem Solving. To this end, two study groups were formed: the first one, involved seven active Mathematics teachers from a state public school, and the second one involved six future teachers from a public university in São Paulo state countryside. The research has a qualitative approach and it is grounded on Romberg's Methodological Model (1992). The instruments used in the field research were questionnaires, interviews, participant observation and the proposed problems in the study groups. Problem Solving was the focus of the discussions, particularly the Methodology of Mathematics Teaching-Learning-Evaluation through Problem Solving. Such Methodology considers the problem as the starting point for building Mathematical knowledge. It is the generator of new concepts, procedures and contents. The participants themselves, teachers and future teachers, were allowed to choose what should be developed in the fifteen meetings of each group by using, as a criterion, the most difficult contents for the students to understand during their school years, namely Algebra, Rational Numbers, Measure, Logarithms, Analytical Geometry and Trigonometry. It is important to point out that the same contents chosen by the active teachers were also considered by the Mathematics future teachers. For data analysis, four thematic axes were built: Problem Solving in learning and in the resignification of mathematical and didacticpedagogical knowledge in Mathematics teacher education; the problematization of Problem Solving in Mathematics learning and teaching practices in classrooms; the Methodology of Mathematics Teaching-learning-evaluation through Problem Solving in Mathematics teacher education; the study groups about Problem Solving as learning spaces for teachers...

O presente trabalho teve como objetivo investigar aprendizagens profissionais docentes que se manifestam em um grupo de estudo apoiado na Metodologia de Ensino-Aprendizagem- Avaliação de Matemática através da Resolução de Problemas. Para isso foram constituídos dois grupos de estudo: o primeiro deles, formado por sete professores de Matemática, em exercício, de uma escola estadual e o segundo, formado por seis futuros professores de uma universidade pública do interior do estado de São Paulo. A pesquisa, de caráter qualitativo, apoiou-se no Modelo Metodológico de Romberg (1992). Os instrumentos utilizados na pesquisa de campo foram questionários, entrevistas, observação participante, além dos problemas propostos nos grupos de estudo. A Resolução de problemas permeou as discussões e, em especial, foi trabalhada a Metodologia de Ensino-Aprendizagem-Avaliação de Matemática através da Resolução de Problemas. Nessa Metodologia, o problema é o ponto de partida para a construção do conhecimento matemático. Ele é o gerador de novos conceitos, procedimentos e conteúdos. Os próprios integrantes, professores e futuros professores, puderam escolher o que deveria ser trabalhado nos 15 encontros de cada grupo usando, como critério, aqueles conteúdos que os alunos mais sentem dificuldade em compreender durante sua escolaridade. Foram eles: Álgebra, Números Racionais, Medida, Logaritmos, Geometria Analítica e Trigonometria. Destaca-se que os mesmos conteúdos indicados pelos professores em exercício também foram considerados pelos futuros professores de Matemática. Para análise dos dados foram construídos quatro eixos temáticos: A Resolução de Problemas na aprendizagem e na ressignificação dos conhecimentos matemático e didático-pedagógico na formação do professor de Matemática; a Problematização da Resolução de Problemas nas práticas de aprender e ensinar Matemática na sala de aula; a Metodologia...
Keywords: Teachers, Training of; Professores - Formação; Professores de matematica; Matemática - Estudo e ensino; Aprendizagem; Ensino - Metodologia